Implementation of Project-Based Learning Model in Improving Students' Learning Independence - Fanani, Andre; Rizal, Syaiful (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Innovation in learning methods is essential to ensure that education runs well. By using the right media, methods, tools, and materials, the learning process can be more interesting, effective, and enjoyable for students. This research intends to find out how the implementation of a project-based learning model can increase students' learning independence in Islamic Religious Education subjects, as well as to identify the obstacles faced by educators in this process. We chose the descriptive qualitative research method to provide a comprehensive picture. The subjects in this research were students and Islamic education teachers of class VIII MTSN 2 Jember. We collected data using interview techniques, observation, and document study methods. We then descriptively analyzed the data through stages of data reduction, data presentation, and conclusion drawing. The results of the research show that the application of the project-based learning model to material regarding the introduction and understanding of believing in prophets and apostles shows enormous potential in increasing student learning independence. In this lesson, the projects involve creating works or engaging in activities that relate to believing in prophets and apostles. With this approach, students not only develop skills in searching for and processing information from various sources but are also able to apply religious values in the context of everyday life in a more meaningful way. The obstacles encountered in implementing this learning model are intensive time management and limited resources.